Determinants of students' entrepreneurial intention to compete in a fast-pitch competition. Issue 6 (18th August 2019) - Jang, Yongseok; Hadley, Brandy; Son, Joon; Song, Chanho
Abstract: Despite the heightened popularity of entrepreneurship education, there remain open questions regarding best practices in co-curricular programs. Using the theory of planned behavior, the authors examine how students' intention is shaped to increase the likelihood of participation in entrepreneurship co-curricular programs. To the best of the authors' knowledge, this study is the first to examine the relation between entrepreneurial identity and entrepreneurial intention theory. They find the popular personality trait, openness, is related to ambition, which reveals the interaction between personal elements (personality/identity) and contextual elements (aspirations to success/intention), a novel finding in the literature. This further illustrates the interconnectedness between the theory of planned behavior and the entrepreneurial event model